Reducing Accidental Dislodgement of the Percutaneous Endoscopic Gastrostomy: A Prospective Trial of the "SafetyBreak" Device. (February 2016) - Rosenberger, Laura H.; Guidry, Christopher A.; Davis, John P.; Hranjec, Tjasa; Johnston, Vonda K.; Wages, Nolan A.; Watson, Christopher M.; Sawyer, Robert G.
Background . The percutaneous endoscopic gastrostomy (PEG) is a ubiquitous feeding tube with high rates of accidental dislodgement, with significant morbidity and health care costs. We hypothesized use of a decoupling device is a safe and effective mechanism to reduce dislodgements. Study Design . We studied a prospective cohort of 100 patients from an academic center. Enrollment included patients requiring PEG tube placement with follow up extending through an individual's lifetime use of their PEG tube. The primary endpoint was accidental dislodgement of the principally placed PEG tube. The secondary endpoint was time to accidental dislodgement of the PEG tube. Results . All 100 patients received the SafetyBreak device and had complete follow-up. Half of the patients had at least a single episode of device decoupling, indicating prevention of dislodgement of the PEG. Eight patients ultimately had dislodgement, resulting in a significantly lower dislodgement rate when compared with a historical cohort ( P = .036) and significantly longer survival of the PEG (log rank = 0.005). When compared with a concurrent cohort (without the device) there was also significantly lower dislodgement rate ( P = .03) and a trend toward longer survival of the PEG (log rank = 0.08). Conclusions . When compared with both a historical and concurrent cohort of patients, the SafetyBreak device reduces accidental dislodgement of PEG tubes. As an increasing number of PEGs are being placed, an increasing number of patients are at risk for dislodgement. The SafetyBreak device is an innovative, economical solution to the problem of accidental dislodgement of the PEG tube.